Analisis resiliensi akademik dan grit pada mahasiswa PGSD - Syahidah, Istnafillah; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2024)
This study aims to determine the ability of academic resilience and grit in PGSD FKIP UNS students. The study used a quantitative descriptive analysis research design. Respondents in this study were 66 Surakarta UNS PGSD students class of 2023 who were selected using proportionate stratified random sampling technique. The instruments used are the academic resilience scale and the grit scale which consists of favorable and unfavorable items. The results showed that 84.6% of students had high academic resilience, and 15.2% of students had moderate academic resilience. In addition, 90.9% of students have moderate grit and 9.1% of students have low grit. There are variations in the level of academic resilience and grit in students. Therefore, it is important for students to train and optimize their non-cognitive abilities, besides that lecturers can also provide support and assistance through guidance services and learning activities they carry out.